2016
DOI: 10.1111/ceo.12796
|View full text |Cite
|
Sign up to set email alerts
|

Steroid‐induced glaucoma treated with trabecular ablation in a matched comparison with primary open‐angle glaucoma

Abstract: Background:To evaluate the outcomes of trabectome-mediated ab interno trabeculectomy in patients with steroid-induced glaucoma (SIG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Akil et al found that with similar preoperative values, IOP reduction in pigmentary glaucoma cases was similar to that in POAG [22]. In our previous studies, patients with pseudoexfoliative-and steroid-induced glaucoma with higher preoperative IOP finally obtained more IOP reduction than age-and gender-matched POAG controls [10,32,33]. Even though preoperative IOP was higher in these patients, the overall success rate was unchanged [10,22,34,35] or even better [34,36] than for POAG patients.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Akil et al found that with similar preoperative values, IOP reduction in pigmentary glaucoma cases was similar to that in POAG [22]. In our previous studies, patients with pseudoexfoliative-and steroid-induced glaucoma with higher preoperative IOP finally obtained more IOP reduction than age-and gender-matched POAG controls [10,32,33]. Even though preoperative IOP was higher in these patients, the overall success rate was unchanged [10,22,34,35] or even better [34,36] than for POAG patients.…”
Section: Discussionmentioning
confidence: 55%
“…The Trabectome surgery was performed as we described previously [10,19]. IOP was measured by Goldmann applanation tonometry.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations